So you want to be president? - St. George, Judith, 1931-2015; Small, David, 1945- (New York : Philomel Books, 2000)
Presents an assortment of facts about the qualifications and characteristics of U.S. presidents, from George Washington to Bill Clinton.
Includes bibliographical references (p. [53]).
Keywords: Presidents -- United States -- Miscellanea -- Juvenile literature; Caldecott Medal; Presidents -- Miscellanea